FILARIASIS DISTRIBUTION AND COVERAGE OF MASS DRUG ADMINISTRATION - Ikha Solikha; M. Sakundarno Adi (Universitas Airlangga, 2019)
Background: Filariasis is still a serious health problem in Indonesia. One of the endemic areas is Demak, which implemented a mass drug administration (MDA) elimination programme in 2016. However, filariasis was still found in 2017-18. Purpose: This research aims to describe the distribution of filariasis and coverage of filariasis MDA in Demak. Method: A case series based on people, time, and place was used as the design of this research. The research was conducted in May-June 2019 using secondary data obtained from the Health Office of Demak based on the results of the MDA programme in the community. The target population of this research comprised residents of Demak from 2016 to 2018. The variables researched were filariasis cases based on gender, age, region, year of MDA implementation, and MDA coverage, which were described based on univariate and spatial analysis. Result: There were 23 filariasis cases in Demak during 2016-18, most of which occurred in the age group 46-60 (39.10%) and in women (60.90%); they occurred in almost all subdistricts of Demak. The MDA coverage of filariasis has reached the target (>85%), but there is one particular area that has decreased MDA coverage where some cases are found each year. Conclusion: Provision of MDA was carried out in 2016-18 but cases of filariasis are still being reported; also, one of these areas has been decreasing its MDA coverage every year.